Aspectos de uma área endêmica para leishmaniose visceral em um município no Maranhão, Brasil - Lago, Rafiza de Josiane Mendes do; Sousa, Isaura Danielli Borges de; Albuquerque, Layana Pachêco de Araújo; Moraes, Francyelle Costa; Aquino, Dorlene Maria Cardoso de (Revista de Epidemiologia e Controle de Infecção, 2020)
Justification and Objectives: Visceral Leishmaniasis (VL) is considered one of the six major priority endemic diseases and of great concern for public health due to its lethality and high incidence. This study aims to describe the socioeconomic, demographic and environmental characteristics of families living in the area with the highest number of cases of VL reported in the municipality of Itapecuru Mirim, Maranhão. Methods: this is a cross-sectional descriptive study. The study included 273 families in the area with the highest number of cases. Results: it was found that the majority of homes were masonry and covered with tile. The houses had four to six inhabitants who lived on an income below the minimum wage. The services of piped water, waste collection and the presence of septic tank were mentioned by 68.13% of the interviewees. Animal breeding and the presence of animals close to the interviewees’ homes was mentioned. VL cases were reported in the family and in the neighborhood. Most respondents were unaware of carrying out control actions for the reservoir and VL vector in the municipality (93.64%). Among families with a history of VL, 56.25% reported that they were not followed up during treatment. Conclusion: the study contributes to understanding the dynamics of infection by VL in the population of the neighborhood, stimulating further studies that encompass the entire municipality or the state. Thus, the data collected serves to alert health managers in the municipality about the problems identified.